On Myzomorphus and M. scutellatus (Coleoptera, Cerambycidae, Prioninae) - Santos-Silva, Antonio; Galileo, Maria Helena M. (Zootaxa, 2015)
The authorship of Myzomorphus is attributed to Sallé (1850) and, consequently, its type species is Myzomorphus scutellatus Sallé, 1850. The year of publication of the work by Sallé is changed from 1849 to 1850. Comments on the syntypes of M. scutellatus are provided.